2011
DOI: 10.1177/0170840611430595
|View full text |Cite
|
Sign up to set email alerts
|

Using Organization Structure to Buffer Political Ties in Emerging Markets: A Case Study

Abstract: We use and extend resource-dependence theory by analyzing how loosely-coupled organizational structures facilitate the management of political ties by business groups in emerging economies. This topic is particularly salient because business groups are a prevalent organizational form in these countries where they face both a high dependence on governments to secure key resources and a unique set of risks associated with political ties. We identify and analyze four buffering mechanisms that enable loosely-coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
151
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(156 citation statements)
references
References 79 publications
3
151
0
1
Order By: Relevance
“…Even in the United States, political connections have been shown to help firms when they deal with regulators (Correia 2014, Yu andYu 2011). In emerging markets, such a buffering effect is seen as an effective mechanism to protect firms from government rent-seeking behavior (Chen et al 2011, Dieleman andBoddewyn 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even in the United States, political connections have been shown to help firms when they deal with regulators (Correia 2014, Yu andYu 2011). In emerging markets, such a buffering effect is seen as an effective mechanism to protect firms from government rent-seeking behavior (Chen et al 2011, Dieleman andBoddewyn 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Even in the United States, political connections have been shown to help firms when they deal with regulators (Correia 2014, Yu andYu 2011). In emerging markets, such a buffering effect is seen as an effective mechanism to protect firms from government rent-seeking behavior (Chen et al 2011, Dieleman andBoddewyn 2012).In contrast, other studies consider these connections from the perspective of the government and emphasize the necessary costs of such linkages for the firm. From this perspective, political connections have a "binding" effect, i.e., they are a mechanism of co-optation, leading firms to be more likely to meet government's requirements McQuarrie 2008, Marquis andQian 2014), and correspondingly expose firms to government expropriation (Boubakri et al 2008, Caprio andCroci 2008).…”
mentioning
confidence: 99%
“…How appropriation by powerful partners happens in the context of politically connected organizations is not extensively addressed in the literature on political ties, although Dieleman and Boddewyn (2012) suggested that firms use organizational design to selectively open and close organizational boundaries to exclude co-opted political ties from internal processes and lessen the negative effects of political ties. However, till date there is little process-research that shows how boundary spanning becomes a contentious process with conflicting needs for more and less permeability that can be successfully exploited by political ties that seek to appropriate firm resources.…”
Section: Political Ties and Appropriationmentioning
confidence: 99%
“…Later extensions of resource dependence have advanced our understanding of the dynamic nature of dependencies (Hillman et al, 2009;Xia, 2011) and the defense mechanisms that organizations can build to deal with appropriation concerns after the tie-formation stage (Inkpen & Currall, 2004;Kirsch, 1996). Research suggests that one way to deal with appropriation concerns is through careful management of organizational boundaries (Dieleman & Boddewyn, 2012;Katila et al, 2008).A crucial aspect of organizational boundaries is permeability, or the degree of organizational openness to the environment (Aldrich & Herker, 1977;Colignon, 1986;Oliver, 1993). Permeability is needed to share resources, for instance through boundary spanning activities or connections, but it also has negative effects (Lin & Si, 2010;Young, Peng, Ahlstrom, & Bruton, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation